2005
DOI: 10.1007/s00466-005-0727-9
|View full text |Cite
|
Sign up to set email alerts
|

Study of non-reactive isothermal turbulent asymmetric jet with variable density

Abstract: In the present study, the effects of inlet isothermal jet geometry on the mixing process with variable density have been investigated numerically. Four density ratios were considered, namely R ρ =7.2, 1.8,1 and 0.66 for He-air, CH4-air, Air-air and CO2-air mixtures respectively. The jets are produced through rectangular and elliptic nozzles with aspect ratio Ar = 2:1. The elliptic and rectangular nozzles have approximately the same exit area as the circular nozzle. A second-order Reynolds stress model (RSM) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…A test of the convergence criteria is shown in Figure 3. In the conservation equations, for the different variables (u, v, k and ), we expressed the scaled residuals respectively by the following relations (12)(13)(14)(15): Also, we expressed unscaled residual of the segregated solver for the continuity equation by:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A test of the convergence criteria is shown in Figure 3. In the conservation equations, for the different variables (u, v, k and ), we expressed the scaled residuals respectively by the following relations (12)(13)(14)(15): Also, we expressed unscaled residual of the segregated solver for the continuity equation by:…”
Section: Methodsmentioning
confidence: 99%
“…He generated a flow with 40 m s -1 velocity in a low-speed air co-flow and scrutinized the effects of the density and nozzle forms on the jet structure. Imine et al (2006) conducted the numerical simulation of an asymmetric, isothermal and turbulent jet discharged in a co-flow with the velocity ratio R u equal to 0.01. They assumed the elliptic approach and the second order model (RSM) in the simulation.…”
Section: Introductionmentioning
confidence: 99%
“…In the mathematical description of the conservation equations, all variables, except the pressure and the density, which are always computed according to Reynolds average, are Favre [10] average (mass-weighted). This quantity is defined as…”
Section: Conservation Equations and Turbulence Modelsmentioning
confidence: 99%
“…Numerous studies indicated the importance of the asymmetric jets in improving the capacity of burners by increasing the combustion efficiency and reducing the emanation of pollutants [1]. This is because it had the ability to increase and improve the efficacy of mixing aggressively and exposes a higher retention rate than circular ones [2]. The results of other works also conducted on the turbulent jet of variable density [3][4][5], confirmed that the mixture efficiency increases when the ratio of density increases.…”
Section: Introductionmentioning
confidence: 99%